STAD and TSTS Learning Mediated with Ice Cream Stick in whole number Operation - Umi Romadiyah (Universitas Negeri Malang, 2015)
Pembelajaran STAD dan TSTS Bermedia Ice Cream Stick pada Operasi Hitung Bilangan Bulat   Abstract: The study aims at describing to describe the implementation of the STAD and TSTS learning models using the Ice Cream Stick as the learning media to increase students' motivation and learning outcomes. The study is conducted using a Classroom Action Research design. The subjects of the study were all 30 students of Class VC of Public Elementary School (SDN) Tunjungsekar 1 Malang. The methods of data collected from observation, interview, tests, and documentation. The study was conducted in two Cycles. The results showed that at the end of the learning motivation measures included in the criteria of high motivation. The learning outcomes show 80% mastery completeness. Key Words: STAD and TSTS learning models, ice cream stick learning media, mathematical operation on whole numbers   Abstrak: Penelitian ini bertujuan untuk mendeskripsikan penerapan pembelajaran STAD dan TSTS bermedia Ice Cream Stick untuk meningkatkan motivasi dan hasil belajar siswa. Penelitian ini menggu-nakan rancangan penelitian tindakan kelas. Subjek penelitian siswa kelas VC SDN Tunjungsekar 1 Malang yang berjumlah 30 orang siswa. Metode pengumpulan data melalui observasi, wawancara, dokumentasi, dan tes. Penelitian dilakukan dalam 2 siklus. Hasil penelitian menunjukkan bahwa pada akhir tindakan motivasi belajar termasuk dalam kriteria motivasi tinggi. Hasil belajar mencapai ketuntasan 80%. Kata kunci: pembelajaran STAD dan TSTS, media ice cream stick, operasi hitung bilangan bulat